2009
DOI: 10.1111/j.1752-8062.2008.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Hematopoietic Microenvironment in Patients with Aplastic Anemia

Abstract: Mechanisms of hematopoietic failure in patients with aplastic anemia (AA) are obscure. We investigate alterations in the hematopoietic microenvironment in AA patients. We present the results of studying mesenchymal stromal cells (MSC), fibroblastic colony-forming units (CFU-F), and adherent cell layers (ACL) of long-term bone marrow cultures (LTBMC) from bone marrow (BM) samples of AA patients. MSC of AA patients proliferated longer than those of donors. In half of the patients' MSC cultures, adipogenesis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 42 publications
3
38
0
1
Order By: Relevance
“…Such a response could be delayed rather than direct. Similar changes were found in patients with aplastic anemia, whose stromal cells were more active than the donor cells .…”
Section: Discussionsupporting
confidence: 75%
“…Such a response could be delayed rather than direct. Similar changes were found in patients with aplastic anemia, whose stromal cells were more active than the donor cells .…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have suggested that BM adipocytes are predominantly negative regulators of the BM microenvironment and are less supportive to hematopoiesis than those of other cell types derived from MSCs, such as osteoblasts . The BM of AA patients often exhibits increasing adipocytes and decreasing osteoblasts, which may be causatively associated with the abnormal hematopoietic niche and impaired hematopoiesis. Here in this study, we confirmed that AA BM‐MSCs are more susceptible to be induced into adipogenic differentiation compared with control BM‐MSCs, which, to some extent, accounts for the fatty phenomenon and defective hematopoiesis in AA marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Aplastic anaemia (AA) is a rare and life‐threatening hematopoietic disorder characterized by hypoplasia and pancytopenia with fatty bone marrow (BM) . The pathogenic factors causally associated with AA may include immune abnormality, quantitative and qualitative defects in hematopoietic stem/progenitors cells and altered marrow microenvironment . Bone marrow mesenchymal stem cells (MSCs) can differentiate into osteoblast, adipocytes and chondrocytes, which together constitute the major cellular components of BM microenvironment providing critical support for hematopoiesis .…”
Section: Introductionmentioning
confidence: 99%
“…It affects mostly children, young adults, and adults, over 60 years of age [17]. This condition can be similar to other hematologic disorders, however, in most cases, the AA is caused by reduced HSCs function, an increase in HSCs apoptosis level, consequently, the decreased of HSCs and hematopoietic progenitors and lastly, microenvironment fat replacement [18,19].…”
Section: Aplastic Anemia: General Featuresmentioning
confidence: 99%